(3GdQbGHI Ydi CehGd GdOhdI GdYGeI hOhQ GdLgGR GdeQcRj ddeMGSHGJ aj GdQbGHI hGdJCKjQ aj GdELQGAGJ GdJCOjHjI (B:s (3OQGSI JWHjbjI (B/s - (3GdCMhd, aJMj eMeO eMeOs ((3GdEScfOQjI (B[(3LeghQjI eUQ GdYQHjI(B] :s (3OGQ GdLGeYI GdLOjOI,s, 2016)
(3jJfGhd GdcJGH MjK jSJbj ehVhY GdHMK CgejJg ef GdCgejI GdHGdZI ddCehGd GdYGeI PGJgG heG JSJhLHg ef aQV QbGHI UGQeI Ydi eaQOGJ Jdc GdCehGd HeG jMbb MSf ESJZdGdgG Ydi CSGS GdaGYdjI hGdGbJUGO hGdcaGjI, eY QHW GdLGfH GdfXQj ddQbGHI GdeGdjI HGdLGfH GdYedj hGdJWHjbj dgG hGdeJeKd aj QbGHI GdLgGR GdeQcRj ddeMGSHGJ Ydi GdCehGd GdYGeI Ke Cfg HYO GdJYOjdGJ GdOSJhQjI aj eUQ YGe (B2007 (3e, heG BdJ Edjg GdCehQ ef OSJhQjI GdNUNUI heG hGLgJg GdQbGHI ef UYhHGJ aj Xd SjGSI GdNUNUI Jdc GdSjGSI GdJj JfGbV aj cKjQI efgG GdMaGX Ydi GdCehGd GdYGeI, hdbO SGYOfj aj gPG GdYed GdeJhGVY eG MUdJ Ydjg ef NHQI YedjI CSGSgG TQa GfJSGHj ddYed HGdLgGR GdeQcRj ddeMGSHGJ eYJQkaG HCf eG CUfYg eG gh EdG NWhI Ydi GdWQjb JaJM GdeLGd CeGe ef jQjO Cf jOdj HOdhg HGdeRjO(B.s
(3HHdjhLQGajI (B: (3UaMI (B691-707.s
Keywords: (3eUQ(B.s -- (3GdLgGR GdeQcRj ddeMGSHGJs -- (3OQGSGJ MGdIs; (3GdQbGHI GdeGdjIs; (3GdeGdjI GdYGeIs -- (3eUQs -- (3JObjb GdMSGHGJs; (3GdeGdjI GdYGeIs -- (3aQfSGs -- (3JObjb GdMSGHGJs; (3GdeMGSHI GdMchejIs -- (3eUQs; (3GdeMGSHI GdMchejIs -- (3aQfSGs; (3GdQbGHI GdeGdjIs -- (3eUQs; (3GdQbGHI GdeGdjIs -- (3aQfSGs